Analisis Bentuk Lahan untuk Menentukan Zona Resapan Air di Lereng Selatan Kawasan Bedugul - DALIMUNTHE, MOHAMMAD RAJU BELLY; SUYARTO, R.; DIARA, I WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Landform Analysis to Determine Recharge Zone Potential in Southern Bedugul Area   Water recharge area is one of the most important part in hydrologic cycle that aimed in passing groundwater, thus determining stability and sustainability of groundwater. The objective of this research to identify the characteristics of landforms on the southern Bedugul Area and determine the potential of the water recharge area in the process of groundwater formation. This research started from August 2017 until May 2018 included the secondary and primary data collection, and to thesis preparation. The method used in this research is survey and map interpretation purposive sampling method with the technique of landform analysis (topography, rock material, permeability, soil texture, and rainfall data) and spatial analysis (Geographic Information System and overlay). Maps that used in overlapping in this research were geological maps, hydrogeological maps, land type maps, and rainfall data.             The result of this study obtained where in research location there are  4 (four) recharge water zones potential criteria, which are good potential, normal natural, start of critical, and critical. As for the research area is dominated by the area with a good potential as a recharge with an area of 3.791,37 ha (63,6 %), areas with normal natural recharge potential of 1.551,18 ha (26,43 %). The area with a start of critical recharge potential of 507,08 ha (7,63 %)  and the critical criteria is only 19,37 ha (0,33 %).